RETRACTED: High-force Mechanical Dynamic Investigation of Natural Fiber Composite Sandwich Panels for Aerospace Design - Alqahtani, Bader (Engineering, Technology & Applied Science Research, 2024)
This article has been retracted at the request of the Editor-in-Chief due to extended similarites with a previously published article. The previously published article is: Alec Redmann, Maria Camila Montoya-Ospina, Ryley Karl, Natalie Rudolph, Tim A. Osswald, "High-force dynamic mechanical analysis of composite sandwich panels for aerospace structures," Composites Part C: Open Access, Vol. 5, Art. No. 100136, July 2021 The authors of this paper failed to provide any reasoning regarding the case.